Бизнес-модели сбыта электрической энергии в развитых и развивающихся странах: особенности и специфика (Путеводитель предпринимателя, 2020)
In this paper the business model of electricity power selling in Western Europe, USA, China, Australia and Latin America is considered. The mechanism of it's producing and application and also economy effect are shown.